Show that the derivative of an odd function is even. That is, if f(-x)=-f(x), then f'(-x)=f'(x). Without using a specific example.

Printable View

- October 25th 2007, 10:57 PMunluckykcshowing f'(-x)=f'(x)
Show that the derivative of an odd function is even. That is, if f(-x)=-f(x), then f'(-x)=f'(x). Without using a specific example.

- October 26th 2007, 03:45 AMPlato

- October 26th 2007, 07:15 AMunluckykc
I don't understand how you got the last line. How does f'(x)=f'(-x)?

- October 26th 2007, 08:14 AMPlato